IDENTITIES AND RELATIONS INVOLVING PARAMETRIC TYPE BERNOULLI POLYNOMIALS - Kurt, B (TWMS journal of applied and engineering mathematics, 2020)
The main purpose of this paper is to give explicit relations and identities for the parametric type Bernoulli polynomials. Further, we give some relations for the generalized Bernoulli polynomials. Keywords: Bernoulli polynomials and numbers, Apostol-Bernoulli polynomials and numbers, Generalized Bernoulli numbers and polynomials, the parametric type Bernoulli polynomials. AMS Subject Classification: 11B68, 11B73, 05A15.